FLAUBERT’S MADNESS IN MEMOIRS OF A MADMAN: RECONCILING AUTOBIOGRAPHY AND FICTION - Fock, Ignac (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
The present article studies the relation between autobiography and fiction in Flaubert’s Memoirs of a Madman, elucidating the characteristics of madness as this work’s main theme and also as a bond permitting the fusion of these two elements in a dichotomy, applicable in fact to Flaubert’s entire opus. Analyzing the novelist’s attitude towards truth and beauty as deduced from Memoirs and also from later works, the author perceives this dualism as a quest for the credibility of beauty, and explains the particularities of Flaubert’s autobiographical presence. He stresses out the paradox of Flaubert glorifying Cartesian reason and simultaneously proclaiming himself as a madman in order to fictionalize and make overwhelming and passionate what is supposed to be autobiographical, thus moderate and trustworthy. Therefore, the madness in Memoirs is merely an arbitrary concept or denomination invented to reconcile reason and sensibility, as well as Flaubert’s other dichotomies caused precisely by this conflict; among them, the dichotomy autobiography-fiction.